2009
DOI: 10.1785/0120080027
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Shallow Shear-Wave Attenuation in the Mississippi Embayment Using Vertical Seismic Profiling Data

Abstract: We used vertical seismic profiling (VSP) data collected in four shallow boreholes (about 40 to 60 m deep) to study the shear-wave attenuation in the Mississippi embayment in southwestern Tennessee. The source was an air-powered hammer that produces repeatable SH waves that were recorded by monitor geophones deployed on the surface very close to the source. The spectral ratio method was used to estimate the shear-wave quality factor (Q S). The method assumes that the amplitudes of the seismic waves decay expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…These values are similar to those calculated by Wang et al (1994) from the distance decay of direct arrivals of critically refracted waves. Ge et al (2009) used a synthetic wave-propagation algorithm that included reverberations within layers, dispersion effects, and anelastic (intrinsic) attenuation to confirm that the estimates of attenuation that they obtained from the spectral-ratio method using VSP measurements were consistent with intrinsic attenuation. They found that they could match the amplitudes of the synthetics using their measured quality factors as estimates of Q in , suggesting that scattering effects are not a significant contributor to their estimates of attenuation and, by analogy, to those of Pujol et al (2002).…”
Section: Seismic Survey Datamentioning
confidence: 95%
See 1 more Smart Citation
“…These values are similar to those calculated by Wang et al (1994) from the distance decay of direct arrivals of critically refracted waves. Ge et al (2009) used a synthetic wave-propagation algorithm that included reverberations within layers, dispersion effects, and anelastic (intrinsic) attenuation to confirm that the estimates of attenuation that they obtained from the spectral-ratio method using VSP measurements were consistent with intrinsic attenuation. They found that they could match the amplitudes of the synthetics using their measured quality factors as estimates of Q in , suggesting that scattering effects are not a significant contributor to their estimates of attenuation and, by analogy, to those of Pujol et al (2002).…”
Section: Seismic Survey Datamentioning
confidence: 95%
“…These surveys were conducted using three methods: vertical seismic profiling (VSP), spectral analysis of surface waves (SASW), and seismic refraction. Pujol et al (2002) and Ge et al (2009) used VSP measurements from a compressed-air-driven hammer to estimate S-wave attenuation in seven shallow (approximately 60 m deep) boreholes located in the region around Memphis. Quality factors were estimated for the 10-50 Hz frequency band from the slopes of the uphole-downhole Fourier spectral ratios.…”
Section: Seismic Survey Datamentioning
confidence: 99%
“…The methods applied on the recorded data are generally based on spectral‐ratio analysis (e.g. Gibbs et al 1994; Parolai et al 2007; Ge et al 2009), matching techniques (e.g. Raikes & White 1984), spectral modelling, measurements of the amplitude decay in the time domain, synthetic modelling, rise time analysis, pulse amplitude method analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A common method used to find the quality factor Q is the spectral ratio technique (e.g., Gibbs et al, 1994;Parolai et al, 2007;Ge et al, 2009). It typically begins by computing the ratio of the Fourier spectra of isolated P and S waves between the surface and downhole seismograms, after taking into account instrument responses and other gain factors not related to attenuation.…”
Section: Methodsmentioning
confidence: 99%